2005
DOI: 10.1017/s003329170400412x
|View full text |Cite
|
Sign up to set email alerts
|

The co-morbidity of anxiety and depression in the perspective of genetic epidemiology. A review of twin and family studies

Abstract: Background. Co-morbidity within anxiety disorders, and between anxiety disorders and depression, is common. According to the theory of Gray and McNaughton, this co-morbidity is caused by recursive interconnections linking the brain regions involved in fear, anxiety and panic and by heritable personality traits such as neuroticism. In other words, co-morbidity can be explained by one disorder being an epiphenomenon of the other and by a partly shared genetic etiology. The aim of this paper is to evaluate the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
180
1
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(204 citation statements)
references
References 64 publications
17
180
1
6
Order By: Relevance
“…46 A review on the comorbidity between anxiety and depression showed that anxiety and depression might be influenced by shared genes, possibly expressed in the personality trait neuroticism. 17 Linkage findings for neuroticism were summarized by Fullerton et al 47 and do not include findings on chromosome 14 in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 A review on the comorbidity between anxiety and depression showed that anxiety and depression might be influenced by shared genes, possibly expressed in the personality trait neuroticism. 17 Linkage findings for neuroticism were summarized by Fullerton et al 47 and do not include findings on chromosome 14 in humans.…”
Section: Discussionmentioning
confidence: 99%
“…11,15 Simple phobia and social phobia have each been investigated once. 9,10 Other anxiety phenotypes 12,14,16 have been based on findings from genetic epidemiological studies indicating a common genetic background for anxiety disorders, 4,17 Thorgeirsson et al 16 considered anxiety disorder or somatoform pain as indicators of affection status. Smoller et al 14 and Kaabi et al 12 constructed new phenotypes of anxiety proneness.…”
Section: Introductionmentioning
confidence: 99%
“…T scores were calculated directly from college-age, sex-specific norms (Robert R McCrae PhD, personal communication, November 14, 2001). Neuroticism (as defined through the NEO) is a well-established, nonspecific risk factor for anxiety and mood disorders (Middeldorp et al, 2005). Given the partial conceptual overlap between AS and N (Cox et al, 1999a;Smoller and Tsuang 1998;Zinbarg et al, 2001), we included neuroticism as a covariate in some models in order to isolate genetic effects more specific to AS.…”
Section: Neo Personality Inventory-revised (Neo-ffi)mentioning
confidence: 99%
“…First, we have taken advantage of the extant literature that suggests shared genetic susceptibility among neuroticism, the anxiety disorders, and major depression (25)(26)(27)(28). Starting with a total of 9270 twin subjects, we used multivariate structural equation modeling to estimate a latent genetic factor for neuroticism that is highly correlated with genetic susceptibility to major depression, generalized anxiety disorder, panic disorder, agoraphobia, and social phobia [see (28) for details].…”
Section: Sample Selectionmentioning
confidence: 99%